(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The advent of digital technology has transformed education, with e-content becoming a pivotal component in teaching and learning. This paper examines the effectiveness of e-content in enhancing mathematics learning concepts and teaching skills. By analyzing current research and case studies, the paper evaluates how e-content supports conceptual understanding, improves teaching methodologies, and addresses challenges and opportunities in its implementation.